Modelling adaptation of thermal reaction norms in fluctuating environments using adaptive dynamics - Suleiman, Abdulrahaman Lawal (Stellenbosch : Stellenbosch University, 2025)
Suleiman, A. L. 2025. Modelling Adaptation of Thermal Reaction Norms in Fluctuating Environments using Adaptive Dynamics. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/a190a40f-2c81-49ca-8cb6-a6296ea6c4dc